2013
DOI: 10.17305/bjbms.2013.2359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endocrine changes in women with the polycystic ovary syndrome during metformin treatment

Abstract: The aim of study was to evaluate endocrine changes in PCOS women during metformin treatment. One hundred women with PCOS, aged 20-40 years were included. A complete hormonal and metabolic pattern was recorded for each subject every 6 months. Metformin treatment after 6 and 12 months significantly reduced weight, BMI, waist circumference, insulin and HOMA-IR (p=0.000) with high differences of variances within repeated measurements. There was significant reduction of PRL, testosterone and estradiol (p=0.000) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
6
38
2
Order By: Relevance
“…Arguments in favor of insulin-like growth factor (IGF) system involvement stem from the relationship of effector proteins of this system to insulin, but mostly from the fact that receptors for these proteins are, to a certain extent, common with insulin receptors. Furthermore, there is consistent data in support of the significant changes in various proteins from this system in PCOS patients (6)(7)(8).…”
Section: Introductionsupporting
confidence: 62%
“…Arguments in favor of insulin-like growth factor (IGF) system involvement stem from the relationship of effector proteins of this system to insulin, but mostly from the fact that receptors for these proteins are, to a certain extent, common with insulin receptors. Furthermore, there is consistent data in support of the significant changes in various proteins from this system in PCOS patients (6)(7)(8).…”
Section: Introductionsupporting
confidence: 62%
“…Androgens, via the AR, play a direct role in the normal growth of ovarian follicles, follicle health, development and ovulation . High serum androgen concentrations are associated with hirsutism, inhibition of follicular development, anovulation and irregular menstruation . However, there are some PCOS patients whose serum testosterone concentration is normal, suggesting possible differences in AR gene activities.…”
Section: Discussionmentioning
confidence: 99%
“…[35] On the same way, a significant reduction in serum levels of FSH in PCOs women was observed after treatment with metformin for (6-12) months. [14] Similarly, silver NPs at (0.5ppm) for longer duration caused a significant elevation in levels of serum FSH, table (2). This result was in consistence with Kong [36] who reported that treatment with Nickel nanoparticles( Ni-NPs) exerted an elevation in serum levels of FSH and LH, and a reduction E 2 associated with significant and dose-dependent in females.…”
Section: Discussionmentioning
confidence: 57%
“…[14] Nanomaterials in general, have unique physiochemical properties, such as ultrasmall size, large surface area to mass ratio, and high reactivity, such properties can be used to overcome some of the limitations found in traditional therapeutic and diagnostic agents. [15] According to the definition used by scientific communities relating to nano-technology, a nanoparticle is defined as a particle with dimension between 1 and 100 nano-meters.…”
Section: Introductionmentioning
confidence: 99%